Control of Technological Processes of Organic Fertilizers Application as a Tool to Ensure Food Safety - BONDARENKO, Anatoly M.; LIPKOVICH, Edward I.; KACHANOVA, Lyudmila S. (Journal of Environmental Management and Tourism, 2018)
Food security of the state is based on the progressive development of the agrarian sector by improving the profitability of its branches. The growth of profitability of the crop sector is possible while building soil fertility by using organic fertilizers. The purpose of the study is to form the aspects of implementation and approaches to the control of the process of organic fertilizers application and to identify their economic substance as a theoretical base in the current conditions of organizational and economic development and management in the agricultural sector. In order to improve the production process management and use of organic fertilizers in the agrarian sector a hierarchical system of resource and product models to optimize production and transportation of organic fertilizers has been developed. The system of resource and product models gives an opportunity to create a strategy of accommodation the technological platforms for the processing organic waste, to optimize transport costs at different levels of the hierarchy of the system implementation, to form a set of measures to increase the level of providing agricultural areas with organics. All this tends to increase the profitability of the crop production branch. To substantiate the effectiveness of the proposed measures to improve the process control of organic fertilizers application divergent forecast scenarios, such as regulatory and extrapolatory (which is subdivided into extrapolatory-inertial and extrapolatory-integrational) have been developed, the consistency of the extrapolatory-integrational forecast scenario has been proved. The designed forecast scenarios are recommended for implementation at various levels of control of technological processes in the agricultural sector, from an economic entity to the state level, using a closed loop process control of the technological processes of production and use of organic fertilizers based on resource and product models.